2011
DOI: 10.1002/pon.1797
|View full text |Cite
|
Sign up to set email alerts
|

Cancer as the cause of changes in work situation (a NOCWO study)

Abstract: A minority of cancer survivors changed employers, occupations, or work tasks because of cancer. Supervisors' support in the form of lightening physically demanding jobs and taking illness into consideration when planning work tasks, and health-care workers' advice on coping at work may help survivors to maintain their jobs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 35 publications
3
27
0
4
Order By: Relevance
“…A similar result was observed in two studies conducted about the impact of cancer diagnosis on income [16,17]. In addition, the disease affected work negatively which is in agreement with studies that presented that the disease affects patients' jobs negatively [18][19][20].…”
Section: Perceptions About the Disease And Quality Of Lifesupporting
confidence: 90%
“…A similar result was observed in two studies conducted about the impact of cancer diagnosis on income [16,17]. In addition, the disease affected work negatively which is in agreement with studies that presented that the disease affects patients' jobs negatively [18][19][20].…”
Section: Perceptions About the Disease And Quality Of Lifesupporting
confidence: 90%
“…That is, CSs make important changes in work that are not captured if only employment status is measured. In our study, we do not know exactly the kind of work changes the employed and self-employed people made, but other Nordic studies [18,34] have shown that changing occupation, employer, or work tasks is common. Since other studies have shown that many CSs struggle with fatigue and consequently reduced physical and mental working capacity [15,17,35], most cancer-related changes in work are probably due to this.…”
Section: Methodological Limitationsmentioning
confidence: 78%
“…These dynamics are more or less supported according to the nature of the initial endowments of human capital, the difficulty of working conditions before the illness but also the type of cancer (site, severity disease) and finally, the nature of the treatment (Mujahid et al, 2011;Lindbohm et al, 2011;Johnsson et al, 2011;Blinder et al, 2012). Past professional biography (unemployment or training episodes) can lead to stigmatizing effects on the careers of individuals (Heckman and Borjas, 1980;Tominey and Gregg, 2005) and, for some social groups, predicts the occurrence of professional cancers.…”
Section: Cancer Onset Effects On Workmentioning
confidence: 99%